Fabrication of pedal powered hacksaw using dual chain drive - Subash, R.; Meenakshi, CM; Samuel Jayakaran, K.; Venkateswaran, C.; Sasidharan, R. (International Journal of Engineering and Technology, 2014)
In this Paper, Pedal operated hacksaw machine which can be used for industrial applications and Household needs in which no specific input energy or power is needed. This project consists of a sprocket arrangement, the crank and slider mechanism, the chain drive. In the mechanism, chain drive  is directly connected to the hacksaw for the processing of cutting the wooden blocks. The objective of the paper is using the conventional mechanical process which plays a vital role. The main aim is to reduce the human effort for machining various materials such as wooden blocks, steel, PVC etc. Keywords: Sprocket Arrangement, Crank and Slider Mechanism.